دراسة محاكاة مزرعة ريحية في عرض الشاطئ السوري - ياخور, يوسف; حمد, نجوى; محمد, علي محمد (Latakia University Journal -Engineering Sciences Series, 2019)
تهدف الدراسة إلى تحديد مدى الاستفادة من الرياح المتاحة في المنطقة البحرية جنوب مدينة طرطوس كمصدر للطاقة يلبي الاحتياجات المتزايدة في القطر العربي السوري. ونظراً لغياب القياسات الحقلية للرياح فوق سطح البحر في تلك المنطقة الأمر الذي شكل عائقاً كبيراً للعديد من الدراسات, فقد تم حساب المتوسط السنوي لسرعة الرياح فوق البحر رياضياً انطلاقا من بيانات محطة الرصد على اليابسة جنوب طرطوس . تضمنت الدراسة ستة احتمالات لإنشاء مزرعة ريحية في عرض شاطئ مدينة طرطوس , استخدم فيها توربينات رياح باستطاعة 5MW,3MW و مسافات مختلفة تفصل بين الصفوف . و قد أظهرت الدراسة بأنه يمكن للمنطقة المقترحة جنوب مدينة طرطوس أن تقدم متوسط استطاعة سنوي يقارب الـ 976MW باستخدام توربينات 5MW موزعة صفياً بفاصل 5.6D . وقد أنجزت الحسابات باستخدام البرامج EXEL ,GUI MATLAB 2010 ,WAsP2010 . The study seeks to determine the extent of utilizing of wind availablility in the coastal region south of Tartous city as an energy source for covering the increasing need for power in Syria. Due to the lack of field measurements of the wind above the surface of the sea in that region, which causes a big hindrance for several studies, the annual average wind speed above the sea has been calculated mathematically based on the data obtained from the monitoring station on land south of Tartous. This study has included six probabilities for establishing a wind farm offshore Tartous city, using different wind turbines (5 MW, 3 MW) and different distances between the rows. This study has also made notable references to the ability of the selected area south of Tartous to give an annual average capacity of approximately 976MW by using turbines 5MW distributed in array form, and the interval distance between the rows is 5.6D. The calculations have been made using the programs ( EXEL, GUI MATLAB 2010, WAsP2010).